Analisis Perbedaan Retail Mix Toko Modern dan Toko Tradisional - Sri Murni Setyawati; Suliyanto Suliyanto; Agus Suroso (Universitas Peradaban, 2018)
This study is to analyze the differences between modern and traditional stores mix retail. The analytical tool used is cluster analysis and different sample pairs. This research will be conducted in Purwokerto. The results showed that elements of customer service in modern stores had significant differences with traditional store customers, the elements of location in modern stores had significant differences with traditional store locations, the store design of modern store had significant differences with traditional store. Merchandise assortments for modern stores have significant differences with traditional store, elements of communication mix in modern store have significant differences with traditional store. Whereas, the elements of pricing in modern shop have no significant differences with the pricing of traditional store.